An Underground Education : The Unauthorized and Outrageous Supplement to Everything you Thought you Knew About Art, Sex, Business, Crime, Science, Medicine, and Other Fields of Human Knowledge - Zacks, Richard (New York Doubleday, 1997)
"Fascinating facts, stories, photos, and images guaranteed to make you laugh, gasp in wonder, and occasionally shudder at the depths of human depravity."
Include Illustration and Index
Keywords: Handbooks, vade-mecums, etc -- Curiosities and wonders